PENGUJIAN HIPOTESIS STATISTIK PENGGUNAAN WARNA CAT TERHADAP PENGARUH HARGA JUAL MOBIL - Hidayat Muhammad Nur; Vadlya Maarif (Universitas Bina Sarana Informatika, 2019)
Abstract - In Indonesia there are several types of cars that are marketed such as LCGC (Low Cost Green Car), Hatchback, Sedan, MPV (Multi Purposes Vehicle), SUV (Sport Utility Vehicle), and Crossover. In addition to types and facilities, car manufacturers also apply different prices for certain types of paint-colored cars. Knowing the reasons for car manufacturers in distinguishing prices from the colors of paint used is not yet sufficiently understood. There are 7 color variants namely Crystal Black Pearl, White Orchid Pearl, Modern Steel Metallic, Red Rallye, Lunar Silver Metallic, Deep Ocean Blue and Purplish Gray Metallic. Special White Orchid Pearl colors are subject to an additional fee of Rp. 3 million, and in addition to the color Rallye Red is subject to an additional fee of Rp.1.5 million from the initial price of Rp.381.5 Million (OTR) for type 1.8 L and P-CVT. Each car manufacturer has its own distinctive color. Therefore, this study provides an analysis of the decision of the producer to provide the selling price of the car calculated using the SWOT method. The coordinates of the probability (O) and strength (S) of producer H are found, meaning that they support an aggressive strategy of producing cars with color variants and quantitative results of the statistical hypothesis showing a positive correlation, with a scale of KR 0.95.Keywords—SWOT, Correlation Coefficient, Hypothesis Statistics, Car Paint Color, Effect of Car Selling PricesAbstrak - Di Indonesia ada beberapa tipe mobil yang dipasarkan seperti LCGC(Low Cost Green Car), Hatchback, Sedan, MPV(Multi Purposes Vehicle), SUV(Sport Utility Vehicle), dan juga Crossover. Selain tipe dan fasilitas, produsen mobil juga menerapkan harga berbeda untuk tipe mobil berwarna cat tertentu. Mengetahui alasan produsen mobil dalam membedakan harga dari warna cat yang digunakan belum cukup dipahami. Terdapat 7 varian warna yaitu Crystal Black Pearl, White Orchid Pearl, Modern Steel Metallic, Rallye Red, Lunar Silver Metallic, Deep Ocean Blue dan Purplish Gray Metallic. Khusus warna White Orchid Pearl dikenakan biaya tambahan sebesar Rp.3 juta, dan selain warna Rallye Red dikenakan biaya tambahan sebesar Rp.1,5 juta dari harga awal Rp.381,5 Juta (OTR) untuk type 1.8 L dan P-CVT. Tiap produsen mobil memiliki ciri khas warna masing – masing. Oleh karena itu, penelitian ini menyampaikan analisa keputusan produsen memberikan harga jual mobil dihitung menggunakan metoda SWOT. Didapati kordinat kuadran peluang(O) dan kekuatan(S) dari produsen H, artinya mendukung strategi agresif memproduksi mobil dengan varian warna dan hasil kuantitatif hipotesis statistik menunjukkan korelasi bersifat positif, dengan skala KR 0,95.Kata kunci—SWOT, Koefisien Korelasi, Statistik Hipotesis, Warna Cat Mobil, Pengaruh Harga Jual Mobil.